Revitalizing Nusantara Traditions through Interactive Cultural Experiences with Augmented Reality Technology - Dawis, Aisyah Mutia; Setiyanto, Sigit; Sadida, Irfan; Bariq, Faiq Fadhil Dzulfiqar (ISB Atma Luhur, 2024)
Advances in digital technology are opening up new opportunities for cultural preservation and promotion. Augmented Reality (AR), with its ability to blend the real and digital worlds, has the potential to bridge the gap between younger generations and the rich cultural heritage of the Nusantara. This research aims to develop an AR application called